Desenvolvimento organizacional e pedagógico do programa Mais Educação na Escola Municipal Elias Montalvão - Pereira, Aline Grazielle Santos Soares (2017)
The extension of the school day implies changes in the pedagogical and administrative organization of the educational institution, through a process that involves the functioning of the existing daily practices. The present paper proposes to find answers to the following question: What needs to be reconsidered in the organization of the pedagogical work after the implementation of the More Education Program (PME) in full-time school? The study was motivated mainly by the interest in investigating how the school that extends its daily school day was conceived in terms of the governmental policies that instituted in Brazil the SME. The aim is to verify to what extent the political presuppositions of the SME, the pedagogical hypotheses of the theoretical field and the school practices present coherences and contradictions in their relations. Thus, the research has as general objective to analyze the organizational and pedagogical development of the More Education Program at the Municipal School Elias Montalvão. Specifically, it aims to: (1) identify the educational and political dimensions expressed in the Articulated Action Plan (PAR), the School Development Plan (PDE-Escola) and the Pedagogical Political Project (PPP); (2) to analyze the organizational and pedagogical development foundations in the PPP and its relation with the SME; (3) to explain the progress and challenges of the SME, based on the views of the SME coordinator and the school council of the school investigated. The methodological course used was the qualitative research, characterized as a case study. As strategies and instruments of data collection, we used: documentary analysis and structured interviews. For the analysis of the data, the content analysis method was employed. The empirical information is evidenced by the PME coordinator's views through individual interview and the school council through a press conference, based on four indicators: dialogue, pedagogical assumptions, didactic materials and the effects of the program in schools. The research presents as a result the reading and the interpretation of the organizational and pedagogical dimensions of a full time school of the Municipal Public School of Education of Aracaju.